QUESTIONING THE EFFECTIVENESS OF POWERPOINT AND LECTURE METHODS IN TEACHING QOWAIDUN NAHWI - Nabila, Nabila; Jundi, Muhammad; Fitrah, Moh. Aldi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
PowerPoint has become a highly popular teaching medium in recent years, supported by various studies showing its high effectiveness in the learning process. However, the opposite has been observed in the teaching of Qowaidun Nahwi at Ma'had Tahfidzul Qur'an al Firqoh an Najiyah Putri. Therefore, this study aims to explain and thoroughly map students' responses and perceptions regarding the use of PowerPoint and the lecture method in Qowaidun Nahwi instruction at the school. This research employs a qualitative approach, with data collection methods including interviews and questionnaires administered to both teachers and students. The findings indicate that, although most students do not find PowerPoint boring, support and interest in this medium are relatively low, with only 58.3% supporting and 61% showing interest. Students tend to better understand the material through direct lectures, which are deemed more effective, with 81% of students viewing PowerPoint as merely a supplementary tool rather than the primary medium. On the other hand, the lecture method supported by the use of a whiteboard garnered higher support, with 73% of students in favor and 83% showing high interest. This method is considered more effective in facilitating the comprehension of complex material like Qowaidun Nahwi, although the integration of interactive methods such as discussions is still necessary to encourage more active student participation in the learning process.